CK19 stabilizes CFTR at the cell surface by limiting its endocytic pathway degradation. Issue 11 (26th August 2019) - Hou, Xia; Wu, Qingtian; Rajagopalan, Carthic; Zhang, Chunbing; Bouhamdan, Mohamad; Wei, Hongguang; Chen, Xuequn; Zaman, Khalequz; Li, Chunying; Sun, Xiaonan; Chen, Song; Frizzell, Raymond A.; et al.
Abstract : Protein interactions that stabilize the cystic fibrosis (CF) transmembrane conductance regulator (CFTR) at the apical membranes of epithelial cells have not yet been fully elucidated. We identified keratin 19 (CK19 or K19) as a novel CFTR‐interacting protein. CK19 overexpression stabilized both wild‐type (WT)‐CFTR and Lumacaftor (VX‐809)–rescued F508del‐CFTR (where F508del is the deletion of the phenylalanine residue at position 508) at the plasma membrane (PM), promoting Cl – secretion across human bronchial epithelial (HBE) cells. CK19 prevention of Rab7A‐mediated lysosomal degradation was a key mechanism in apical CFTR stabilization. Unexpectedly, CK19 expression was decreased by ~40% in primary HBE cells from homogenous F508del patients with CF relative to non‐CF controls. CK19 also positively regulated multidrug resistance–associated protein 4 expression at the PM, suggesting that this keratin may regulate the apical expression of other ATP‐binding cassette proteins as well as CFTR.—Hou, X., Wu, Q., Rajagopalan, C., Zhang, C., Bouhamdan, M., Wei, H., Chen, X., Zaman, K., Li, C., Sun, X., Chen, S., Frizzell, R. A., Sun, F. CK19 stabilizes CFTR at the cell surface by limiting its endocytic pathway degradation. FASEB J. 33, 12602–12615 (2019). www.fasebj.org